Characteristics of human spermatozoa harvested in culture media with and without serum proteins - Ghofraan A. Ata’Allah,; Noor Azmi Mat Adenan,; Nuguelis Razali,; Siti Khadijah Idris,; Jaffar Ali,; Kannappan Palaniappan,; Rosliza Saad,; Krishnan Kanniah, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was aimed to determine the efficiency of synthetic protein-free media in spermatozoa washing, preparation and retention of the activity of washed spermatozoa over short periods in vitro. Normozoospermic semen samples (n = 71) were equally apportioned and washed using synthetic protein-free medium (PFM), minimum essential medium + HSA (MEM) or commercial protein-containing medium (CPC). Washed spermatozoa were cultured in vitro using PFM, MEM or CPC media and held for 24 hrs at 4°C, 15°C, 22°C or 37°C. Spermatozoa activity was evaluated at 0 hr, 4 to 7 hrs and 24 hrs post-wash. The effects of PFM on spermatozoa motility, vitality, membrane integrity and DNA fragmentation level were not significantly different from that of MEM and CPC media at 0 hr, 4 to 7 hrs and 24 hrs post-wash in vitro. Synthetic PFM, MEM and CPC retained spermatozoa activity highest when specimen were held at 22°C and it was significantly higher (p < 0.05) than that at 37°C after 24 hrs incubation in vitro. However, no significant changes (p > 0.05) were noted in spermatozoa DNA fragmentation (SDF) levels when specimen were held at 22°C or 37°C at 4 to 7 hrs and also after 24 hrs post-wash in vitro in all media. The use of synthetic PFM as an alternative to the commercial protein-containing media in human spermatozoa washing and preparation procedure for an efficient and safer (Assisted Reproduction Technology) ART outcome. Spermatozoa activity can be successfully retained at room temperature post-wash over short periods; spermatozoa may lose viability rapidly if held for long hours at 37°C in all media.